Can we predict obstetric anal sphincter injury?. (March 2017) - Drusany Starič, Kristina; Bukovec, Petra; Jakopič, Katja; Zdravevski, Eftim; Trajkovik, Vladimir; Lukanović, Adolf
Abstract: Objective: The aim of the study was to identify primiparous pregnant women with a higher risk for obstetric anal sphincter injuries (OASIS) based on obstetric characteristics (risk factors). Study design: In the retrospective case control study primiparous women were examined using endoanal ultrasonography (EUS) for OASIS identification 6–12 weeks after delivery. Obstetric characteristics for OASIS were collected from the mothers' medical records. The univariate analysis of maternal (age at delivery, maternal height, weight, BMI), infant (length, weight and head circumference) and birth (pregnancy duration, labour and delivery duration, episiotomy, vacuum extraction and oxytocin augmentation) risk factors, Pearson correlations and information gain were carried out. The cut-off values for the aforementioned risk factors divided the patients into groups with higher and lower risk of OASIS. Results: The data of 84 primiparous women with OASIS, and 58 without, were analysed. Those newborns born to women in the OASIS group were heavier (P < 0.05), with the cut-off at 3420 g (72% probability of OASIS), had a larger head circumference (P < 0.001), cut-off at 36 cm (84% probability of OASIS), and were longer (P < 0.05), cut-off at 50.5 cm (74% probability of OASIS). The maternal age and body mass index (BMI) were risk factors for OASIS (P < 0.05 and P < 0.05, respectively) with a probability of 83% in women younger than 27.5 years and a 78% probability if BMI was higher than 28 kg/m 2 . The incidence of OASIS was not higher in women with episiotomy or vacuum extraction, but it was higher in oxytocin augmentation (P < 0.031). Conclusion: The findings can assist in identification of pregnant women with a higher risk of OASIS who require special attention at delivery to prevent it. In high risk women EUS is indicated to identify and treat possible OASIS as early as possible in order to prevent anal incontinence.